New insights into freshwater ascomycetes: discovery of novel species in diverse aquatic habitats - Lu Li; Lu Li; Lu Li; Darbhe Jayarama Bhat; Darbhe Jayarama Bhat; Hong-Bo Jiang; Hong-Bo Jiang; Hong-Bo Jiang; Hong-Bo Jiang; Jun-Fu Li; Jun-Fu Li; Jun-Fu Li; et al. (Frontiers in Cellular and Infection Microbiology)
During investigations of freshwater fungi in Hunan and Yunnan provinces, China, Chaetopsina yunnanensis sp. nov. (Nectriaceae), Parafuscosporella hunanensis sp. nov. (Fuscosporellaceae), and Pleurotheciella yunnanensis sp. nov. (Pleurotheciaceae) were discovered on submerged decaying wood and branches. Based on phylogenetic analyses, C. yunnanensis formed a separate branch with Chaetopsina pinicola and nested among other Chaetopsina species in Nectriaceae (Hypocreales). Furthermore, hitherto known Chaetopsina beijingensis shared the same branch with Chaetopsina fulva, a type species of the genus, demonstrating their conspecific status. Therefore, C. beijingensis is formally synonymized under C. fulva, with an amended species circumscription. Pa. hunanensis formed a well-separated subclade with the ex-type strain of Parafuscosporella mucosa and clustered with other Parafuscosporella within Fuscosporellaceae (Fuscosporellales). In addition, the genus Parafuscosporella is treated as distinct from Vanakripa due to a lack of phylogenetic evidence in clarifying their congeneric status with the latter. Pl. yunnanensis is found to be sister to Pleurotheciella saprophytica, forming a subclade with Pleurotheciella dimorphospora within the Pleurotheciaceae (Pleurotheciales). Morphologically, C. yunnanensis fits well with the generic concept of Chaetopsina in forming a holomorphic state with hyphomycetous asexual morph producing pigmented, setiform conidiophores, phialidic conidiogenous cells, hyaline conidia, and nectria-like sexual morph. Pa. hunanensis fits well with Parafuscosporella in having acrogenous, apiosporous, versicolored, obovoid to obpyriform conidia. In contrast, Pl. yunnanensis resembles Pl. dimorphospora in forming asexual dimorphism with two types of conidia (Type I, brown, muriform/phragmosporous conidia; Type II, hyaline, amerosporous/didymorsporous conidia). The novelty of taxa is explained with detailed descriptions, photo-micrographic illustrations, polymorphism, and multigene phylogenetic analyses of Bayesian inference and maximum likelihood criteria.